(untitled) (Journal of the Spanish Institute for Strategic Studies, 2018)
Most major rivers basins are shared between two or more countries, given that the administrative boundaries often do not coincide with the natural ones. In many cases, water is not managed at basin scale, which is the natural unit of water on the surface of the Earth. Several neighbouring countries that share river or lake basins are immersed in conflicts over water. However, shared water management constitutes a powerful mechanism for international cooperation if it is aimed at satisfying human and environmental needs, what has been coined “geowater”